7th annual CVMBS research day scientific proceedings - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, author; Phi Zeta, author (Colorado State University. Libraries, 2006)
Includes abstracts only of the oral sessions and posters.
7th annual CVMBS research day
Colorado State University, College of Veterinary Medicine and Biomedical Sciences, 7th annual CVMBS research day scientific proceedings
Held in the Hilton Hotel on February 4, 2006, Fort Collins, Colorado.
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses